940. Impact of Using Arts Programming to Support Treatment in Adolescents Living with HIV in Eswatini. (31st December 2020) - Agrawal, Vedika; Ness, Tara; Small, Amanda; Simelane, Tandzile T; Lukhele, Bhekemusa; Dlamini, Sandile; Petrus, Jamie
Abstract: Background: Adolescents and young adults with HIV are a unique population given the distinct psychosocial challenges of their age-group coupled with having a stigmatizing disease. In 2018, approximately 1.6 million adolescents were living with HIV worldwide, with the highest HIV prevalence found in Eswatini. As this group struggles more than any other age-group with medication adherence, novel interventions that are peer-inclusive and empowering should be explored to support their treatment. Methods: We piloted a theater camp to determine the impact of fostering creative expression amongst adolescents and young adults enrolled at our HIV clinic in Mbabane, Eswatini. A two-week camp was conducted in collaboration with a non-profit organization of professional teachers, actors, and musicians. We emphasized enrollment of patients struggling with medication adherence, teen mothers, and those on second-line antiretroviral treatment. Twenty individuals (ages 12-23) participated in self-expression activities, story development, and a final play performed for the community. To assess impact, we compared viral loads pre- and post- camp as well as surveyed participants on effect of participation on areas such as personal stigma, sense of community, and confidence. Results: Of those who participated, 25% showed a substantial decrease and 10% a substantial increase in viral load after the camp (>0.1 log10 change). Those who completed the survey (n=18) felt the camp helped them with confidence (13/18), teamwork (13/18), and friendships (11/18). Quotes from participants reinforced this growing sense of community, confidence, and decreased personal stigma. One wrote "theater camp helped me know that I can do a lot of things in life to achieve my future goals although I am HIV positive" and another stated "it made me not feel sorry for being an HIV positive person." Conclusion: Our pilot program demonstrates creative arts programming has beneficial psychosocial effects, aids in community building, and potentially enhances the effectiveness of medical treatment. Further programs and studies should continue to investigate creative arts as an avenue for treatment support, self-expression, and community building among vulnerable populations such as adolescents and young adults with HIV. Disclosures: All Authors : No reported disclosures